Metabolic reprogramming of human visceral fat-derived stem cells - Sindi (2015)
The obesity pandemic prompted the search for novel preventive and therapeutic interventions. The divergent biological characteristics of subcutaneous and visceral white adipose tissue depots can be attributed to their distinctive transcriptome and secretome down to the stem cell level. It is widely known that visceral adipose stem cells (VS-ASCs) are less adipogenic as compared to subcutaneous adipose stem cells (SC-ASCs) and earlier studies identified the secreted Matrix GLA protein (MGP) as highly expressed in VS-ASCs. In this study, we investigated its role in regulating adipogenesis of VS-ASCs. We demonstrated increased expression of MGP in VS-ASCs compared to SC-ASCs across different donors. Elevated MGP level in VS-ASCs during adipogenesis suggests that MGP could negatively regulate differentiation. However, knockdown of MGP in VS-ASCs reduced adipogenesis, which could be caused by attenuated cell growth upon MGP loss-of-function. We then evaluated if the paracrine factors secreted by ASCs could influence adipogenesis. VS-ASCs derived conditioned medium (CM) did not influence SC-ASCs adipogenesis. Remarkably, SC-ASCs derived conditioned medium promoted adipogenesis of VS-ASCs in a dose-dependent manner and the biologically active component would warrant further investigation. Taken together, our results provide support for future utilization of ASCs and their secretome as potential therapeutic modalities against obesity.